Financing risk management in agriculture in the light of the Common Agricultural Policy* - Lipińska, Izabela (Wydawnictwo Naukowe UAM, 2016)
The last reform of the Common Agricultural Policy has resulted, among other things, in a new institutional legal framework for production risk management. The paper discusses the issues connected with the role of the EU legislator in shaping various forms of financial support as well as the position of the State in applying the state aid. Additionally, the recent changes made to legal provisions governing the support are stressed and the sufficiency of the support offered assessed. The applicable EU legal regulations establish a wide range of subsidised instruments and special protection for agricultural producers. They do not, however, make the producers take over the responsibility for risk management. It is thus concluded that applied ad hoc state aid limits the applications of risk management instruments among farmers.

Il risultato della recente riforma della politica agricola comune è costituito tra l’altro da una determinazione di un nuovo istituzionale quadro giuridico per la gestione dei rischi in produzione agricola. L’oggetto dell’articolo è una problematica legata al ruolo del legislatore dell’Ue nel formare varie forme di sostegno finanziario, così come alla posizione dello Stato nell’accordare gli aiuti pubblici. Inoltre l’autrice cerca di indicare cambiamenti avvenuti di recente nella loro struttura giuridica e di valutare se il sostegno disponibile sia sufficiente. Le regolazioni dell’Ue in vigore prevedono un ampio ventaglio di strumenti sovvenzionati e una tutela speciale per i produttori agricoli. Tuttavia, esse non portano a far assumere ad essi la responsabilità per la gestione del rischio. Nella parte conclusiva l’autrice sostiene che gli aiuti pubblici applicati ad hoc portano a limitare l’applicazione degli strumenti di gestione del rischio presso gli agricoltori.
Il finanziamento della gestione dei rischi in agricoltura alla luce della politica agricola comune